VD_FINDINFO HC / 2011 / 536 vom 5. September 2011 - VD Tribunal cantonal (2011)
DIVORCE, MESURE PROVISIONNELLE, DROIT DE GARDE, PLACEMENT D'ENFANTS DANS UNE INSTITUTION | 176 al. 3 CC, 310 al. 1 CC, 310 CC